Pengaruh Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan Hotel Grand Rocky Bukittinggi - Putri, Sari Dewi; Silfeni, Silfeni; Yuliana, Yuliana (Journal of Home Economics and Tourism, 2016)
The purpose of research is to determine the working environment and job satisfaction of employees in the Grand Rocky Hotel Bukittinggi. This research is a type of kausal. This research was measured in with two variables working environment and Employee Job Satisfaction. Population of this research all employees of the Grand Rocky Hotel Bukittinggi totaling 114 people. Technique of sampling is proportional sampling, and sample in this research amount to 54 people. Data was collected using a questionnaire (questionnaire) using a Likert scale consists of 81 items that have been tested the validity and reliabilitasnya. The result of this research is Work environment is in good category (57%), Job Satisfaction employees are in enough category (72%), such as missing more (89,5) job satisfaction influence different factor. Key Word : job satisfaction, work environment, employees